Postpartum lactation counseling and exclusive breastfeeding: analysis of the 2017 Indonesian Demographic and Health Survey - Warantika Rikma Yuniarini; Elisabeth Siti Herini; Abdul Wahab (Paediatrica Indonesiana, 2021)
Background The percentage of exclusive breastfeeding in Indonesia on 2018 dropped from 39.8% in infants aged 0 monthsto 15.3% in infants aged 5 months. According to the 2018 Indonesian Basic Health Research Survey (Riskesdas), an average of 37.3% of infants were exclusively breastfed until the age of 6 months. This rate is far from the target of 80% by Ministry of Health of Indonesia. Objective To assess for an association between postpartum counseling and the practice of exclusive breastfeeding in Indonesia. Methods This retrospective cohort study used data from the 2017 Indonesian Demographic and Health Survey (IDHS). The sample comprised 258 infants aged 6 months. Postpartum counseling and other variables were analyzed for possible associations with exclusive breastfeeding by Chi-square test; risk ratios (RR) with 95% confidence intervals (CI) were calculated. Logistic regression test was used to analyze for adjusted odds ratios. Results In 6 months period, the percentage of subjects who received postpartum counseling was 59.7% and who exclusively breastfed was 18.8%. There was no significant association between postpartum lactation counseling and exclusive breastfeeding. However, there were significant associations between exclusive breastfeeding and not using currently as well as maternal residence in rural areas. Conclusion Postpartum counseling on breastfeeding lacks a significant association with exclusive breastfeeding practice at 6 months of age. Therefore, the Ministry of Healthshould reevaluate the implementation of its counseling services.